Complement and NfL associations with brain structure and functional connectivity alterations in presymptomatic and symptomatic GRN mutation carriers. (1st February 2022) - Flagan, Taru M.; Chu, Stephanie A.; Häkkinen, Suvi; McFall, David; Heller, Carolin; Rohrer, Jonathan D; Brown, Jesse A.; Lee, Alex Jihun; Pasquini, Lorenzo; Mandelli, Maria Luisa; Gorno‐Tempini, Marilu; Appleby, Brian; et al.
Abstract: Background: Progranulin ( GRN ) mutations cause autosomal dominant frontotemporal lobar degeneration. Clinical trials for GRN ‐targeted therapies are underway, yet reliable biomarkers to predict onset and track disease progression remain elusive. Task‐free functional MRI (tf‐fMRI) connectivity may be more sensitive than structural measures for detecting presymptomatic changes (Dopper, 2014; Premi, 2016). Presymptomatic GRN feature tf‐fMRI hyperconnectivity that is more pronounced in older carriers presumably closer to symptom onset, suggesting hyperconnectivity may be a harbinger of disease (Lee, 2019). To aid the interpretation of hyperconnectivity, we explored relationships of structural and tf‐fMRI measures with candidate fluid biomarkers for GRN : CSF complement proteins C3b and C1q, which drive neurodegeneration in GRN ‐/‐ mice (Lui, 2016) and plasma neurofilament light chain (NfL), a marker of axonal injury. Method: We studied 20 symptomatic GRN (Sx), 39 presymptomatic GRN (preSx), and 67 healthy‐controls (HC). Cross‐sectional CSF C3b, C1q, and plasma NfL concentrations were compared between groups. Correlations controlling for age assessed relationships between fluid biomarkers and symptom severity (CDR ® +NACC‐FTLD box score). Voxelwise multiple regression models examined interactions between fluid biomarkers and gene status on grey matter probability maps (GM) and voxelwise tf‐fMRI whole‐brain weighted degree (WBD) maps. Result: Complement concentrations were similar between Sx, preSx, and HC. Across all GRN, C3b concentrations increased with symptom severity (r=0.34, p=0.04). In Sx, but not preSx, higher C3b was associated with increased WBD in medial‐frontal regions, left insula, and thalamus compared to HC. Sx had higher NfL concentrations compared to preSx and HC. Across all GRN and in Sx, higher NfL was associated with greater symptom severity (r=0.60, p<0.001; r=0.72, p<0.001). In Sx, higher NfL was associated with lower GM in precuneus and bilateral frontoinsular cortices, but not WBD, compared to HC. In preSx, higher NfL was associated with increased WBD in thalamus and right temporal regions, but not GM, compared to HC. Conclusion: C3b and NfL concentrations correlated with symptom severity. C3b concentrations were associated with tf‐fMRI connectivity alterations in Sx while NfL concentrations were associated with connectivity alterations in preSx. Longitudinal studies are needed to determine temporal relationships between altered connectivity, atrophy, complement, NfL rise, and symptom onset.